Desenvolvimento econômico e condições de vida: a força de uma ideia e uma ideia força na obra de Roberto Simonsen - Freitas Junior, Moacir de [UNESP] (Universidade Estadual de Ponta Grossa (UEPG), 2013)
The intent of this article is to investigate the contribution of Roberto Simonsen for the knowledge and the improvement of living conditions of workers in Brazil. Our hypothesis is that the intellectual contributed in a fundamental way to the theme of the living conditions of workers, especially workermen, was inserted into a broader agenda, that of “national-developmentalism”, to which it also contributed signifi cantly, as we will discuss throughout this work, being the subject at the center his theories, the core, the foundation of which he went to build the corollary of ideas about Brazil and the world that consecrated him as a great thinker in Brazil.

O intento deste artigo é investigar a contribuição de Roberto Simonsen para o conhecimento e a melhora das condições de vida dos trabalhadores no Brasil. Nossa hipótese é a de que o intelectual contribuiu de maneira fundamental para que o tema das condições de vida dos trabalhadores, especialmente dos operários, fosse inserido em uma agenda mais ampla, a do nacional-desenvolvimentismo, para a qual também contribuiu de maneira signifi cativa, conforme debateremos ao longo deste trabalho, sendo o tema o centro de suas teorias, o cerne, o alicerce do qual partiu para erguer o corolário de ideias sobre o Brasil e o mundo que o consagraram como um grande pensador no Brasil.
Economical development and living conditions: the strength of an idea and a key idea in the work of Roberto Simonsen
Keywords: Industrialization; Living conditions; National developmentalism; Industrialização; Condições de vida; Nacional-desenvolvimentismo